Insufficient Folding of Type IV Collagen and Formation of Abnormal Basement Membrane-like Structure in Embryoid Bodies Derived from Hsp47-Null Embryonic Stem Cells - Matsuoka, Yasuhiro (The American Society for Cell Biology, 2004)
Hsp47 is a molecular chaperone that specifically recognizes procollagen in the endoplasmic reticulum. Hsp47-null mouse embryos produce immature type I collagen and form discontinuous basement membranes. We established Hsp47(-/-) embryonic stem cell lines and examined formation of basement membrane and production of type IV collagen in embryoid bodies, a model for postimplantation egg-cylinder stage embryos. The visceral endodermal cell layers surrounding Hsp47(-/-) embryoid bodies were often disorganized, a result that suggested abnormal function of the basement membrane under the visceral endoderm. Rate of type IV collagen secretion by Hsp47(-/-) cells was fourfold lower than that of Hsp47(+/+) cells. Furthermore, type IV collagen secreted from Hsp47(-/-) cells was much more sensitive to protease digestion than was type IV collagen secreted from Hsp47(+/+) cells, which suggested insufficient or incorrect triple helix formation in type IV collagen in the absence of Hsp47. These results indicate for the first time that Hsp47 is required for the molecular maturation of type IV collagen and suggest that misfolded type IV collagen causes abnormal morphology of embryoid bodies.